Perancangan Antena Omnidirectional Untuk Pengiriman Data Wireless - Ilham Ilham; Ery Safrianti; Yusnita Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
The antenna has a big role either in high or low frequency of wireless communication. In transmission process, antenna also become a determinant factor of successful communication between transmitter and receiver. In this project, we will design an omnidirectional antenna that will be connected with electrical unit measurement device. To make analyzing process easier, ansoft hfss 13.0 software will be used. The simulation results show that the antenna can work well at frequency of 433 MHz, return loss 13.3955, gain 2.71 and VSWR 1.5. the simulated radiation pattern agrees well with measured radiation pattern that is omnidirectional.Keywords : Keywords : wireless, omnidirectional, VSWR, prototype